Epitaph for an era politics and rhetoric in the Carolingian world - Jong, Mayke de 1950- (Cambridge University Press, 2019)
Machine generated contents note: 1. Introduction; Part I. History: 2. Interconnected lives; 3. Between the cloister and the court; Part II. Rhetoric: 4. Lament and dialogue; 5. Strategies of persuasion; 6. What's in a name?; Part III. Politics: 7. Radbert and the rebellions; 8. For God, King and country; 9. The world they had lost; Conclusion.